Evaluating the Role and Efficacy of Plerixafor in Rescue Mobilization of Autologous Peripheral Blood Stem Cells - E Prunier1; D Caillot; C Legouge; S Limat; P Helias; J Fontan; M Heczcko; A Brion; E Ferrant; P Delaby; E Daguindau; M Tavernier; et al. (Journal of Hematology and Oncology Research, 2015)
In autologous hematopoietic stem cell transplantation patients for whom granulocyte-colony stimulating factor fails to mobilize a sufficient number of peripheral blood stem cells, plerixafor proposes an option for successful rescue mobilization. This paper evaluates the efficacy of plerixafor to mobilize peripheral blood stem cells (PBSCs) in patients who failed previous mobilization with G-CSF alone, by retrospectively analysing the PBSC results from lymphoma and myeloma (MM) patients between 2006 and 2011. Patients were classified according to the CD34+ cells/kg yield collected by apheresis: < 2 x 106 CD34+ cells/kg was considered collection failure, whereas ≥ 5 x 106 CD34+ cells/kg was considered good mobilization. 797 patients underwent one or more apheresis. The first mobilization success rate was 82%; 140 patients proved to be poor mobilizers. Suboptimal first mobilization was significantly associated with age >50 years (p=0.005) and the absence of chemotherapy in prior PBSCs stimulation (p=0.04). 149 rescue protocols were used in the 140 poor mobilizers, and 71 patients received plerixafor. In univariate analysis the remobilization rate without plerixafor was 42% and increased to 65% when plerixafor was added. In multivariate analysis, plerixafor administration reduced the PBSC remobilization failure risk by a half (OR=0.47). The median value of CD34+ cells/kg in transplants increased from 1.43 (range, 014.03) without plerixafor to 3.85 (range, 0–18.25; p=1 x 10-4) with plerixafor. There were more good mobilizers after plerixafor use (35% with plerixafor versus 15% without plerixafor; p=0.005). Plerixafor efficacy was similar for lymphoma (60% remobilization) and MM (80%; p=0.12). These data show that plerixafor was effective in poor mobilizers and that it synergized with G-CSF to improve the quantity of collected PBSCs. Plerixafor also increased transplant feasibility by 23%. While the clinical results of this study are promising, economic data were not taken into account and there is a need for real work concerning the cost-effectiveness of this treatment. We propose a subsequent study in which the economic efficacy of plerixafor’s use is evaluated based on the financial aspects of the treatments received by the cohort evaluated in this paper.
Keywords: Autologous transplantation